2005
DOI: 10.1002/pssc.200461331
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry characterization of amorphous aluminum nitride and indium nitride thin films

Abstract: PACS 78.20.Ci, 78.66.Fd We have measured and analyzed the optical characteristics of a series of amorphous aluminum nitride, aAlN, and amorphous indium nitride, a-InN, thin films deposited on crystalline silicon, c-Si (111), by RF reactive magnetron sputtering at temperature T < 325 K. Spectroscopic Ellipsometry measurements were carried out at two angles of incidence, 70 o and 75 o , over the wavelength range 300-1400 nm. The measured ellipsometric data were fitted to models consisting of air / a-AlN/Sio 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In the NIR to UV energy region, we have instigated Adachi's [16,20] optical dispersion mechanisms and extorted ( ) ε ω  or ( ) n ω  by exploiting the modified [32] model dielectric functions. The simulated energy dependent optical constants for the binary and ternary alloys compared favorably well with the existing FIR-SE and other experimental [22][23][24][25][26][27][28][29] data. These results are proven valuable for accurately assessing the film thickness d from the polarization dependent reflectivity R(λ) and transmission T(λ) spectra of ultrathin Cd 1-x Zn x Te/GaAs (001) epifilms.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the NIR to UV energy region, we have instigated Adachi's [16,20] optical dispersion mechanisms and extorted ( ) ε ω  or ( ) n ω  by exploiting the modified [32] model dielectric functions. The simulated energy dependent optical constants for the binary and ternary alloys compared favorably well with the existing FIR-SE and other experimental [22][23][24][25][26][27][28][29] data. These results are proven valuable for accurately assessing the film thickness d from the polarization dependent reflectivity R(λ) and transmission T(λ) spectra of ultrathin Cd 1-x Zn x Te/GaAs (001) epifilms.…”
Section: Discussionsupporting
confidence: 66%
“…A traditional approach of multilayer optics is used to simulate polarization dependent reflectivity [R(λ)] and transmission [T(λ)] spectra for ultrathin Cd 1-x Zn x Te/GaAs (001) epifilms of thickness ranging between 22 nm ≤ d ≤ 1 µm. Theoretical results of R(λ) and T(λ) are compared, discussed and contrasted amongst the available experimental data [22][23][24][25][26][27][28][29] with concluding remarks presented in Section 7. An accurate assessment of film thickness by reflectivity study has offered a credible testimony for characterizing epitaxially grown nanostructured materials of diverse technological importance.…”
Section: Introductionmentioning
confidence: 99%
“…Khoshman and Kordesch (Khoshman and Kordesch 2005) worked on amorphous AlN and found that the refractive index in the near infrared region (780.5 nm) is 1.95. This value of the index of refraction of amorphous AlN is obtained using the films deposited in the same deposition system and the same conditions that we used for our work.…”
Section: Amorphous Aln:tm (Ti) On Optical Fiber In a Cylindrical And mentioning
confidence: 99%
“…3 Results and discussion Since we know exactly the values of indices of refraction and the polarized optical properties of AlN and InN thin films over a wide wavelength range [4,5], it is therefore very easy to apply Mouchart conditions [1,2] to build a double layer antireflection coating of nitride materials. Because the index of refraction of InN is always greater than AlN and quartz, we first sputtered InN onto the quartz substrate as an inner layer and AlN was sputtered as an outer layer to build one bilayer structure in the periodic multilayer system.…”
mentioning
confidence: 99%
“…Because the index of refraction of InN is always greater than AlN and quartz, we first sputtered InN onto the quartz substrate as an inner layer and AlN was sputtered as an outer layer to build one bilayer structure in the periodic multilayer system. This system was optimized at 500 nm where the indices of refraction of InN and AlN are 2.35 and 1.94, respectively [4]. Further, the thicknesses of each layer in the bilayer system were chosen according to the destructive interference condition (Eq.…”
mentioning
confidence: 99%